HUBUNGAN PERAN ORANG TUA DENGAN KECERDASAN NATURALIS PADA ANAK USIA 5-6 TAHUN DI PANTAI MUARO LASAK PADANG - Gustiyono, Reynada; Ismaniar, Ismaniar (Jurnal Family Education, 2023)
The background of this research is the low naturalist intelligence in early childhood 5-6 years at Muaro Lasak Padang Beach, this is presumably due to the lack of parental involvement. The purpose of this research is to describe the role of parents in naturalist intelligence in early childhood, a description of naturalist intelligence in early childhood, and the relationship between the role of parents and naturalist intelligence in early childhood 5-6 years at Muaro Lasak Padang Beach. This type of research is correlational quantitative, the study population is parents who have children aged 5-6 years, namely 37 people, and 80% of the research sample is taken, namely 30 people, using a stratified random sampling technique. Data collection techniques with questionnaires and data collection tools with a questionnaire containing a list of statements. The data analysis technique of this research uses the percentage and product moment formulas. The results of this study indicate that: 1) Description of the role of parents in the development of early childhood naturalist intelligence in Muaro Lasak? 2) Description of the development of naturalist intelligence in early childhood in Muaro Lasak? 3) Is there a relationship between the role of parents and the naturalist intelligence of early childhood 5-6 years at Muaro Lasak Padang Beach? It is hoped that parents will improve their early childhood naturalist intelligence, so that they can do it properly and correctly. In order for early childhood to carry out naturalist intelligence properly and to the maximum extent possible, the school environment and the surrounding community must also play a role. Keywords: the role of parents, early childhood naturalist intelligence